Quality of life after hepatic resection. Issue 3 (5th February 2018) - Studer, P.; Horn, T.; Haynes, A.; Candinas, D.; Banz, V. M.
Abstract : Background: Long‐term quality of life (QoL) after liver resection is becoming increasingly important, as improvements in operative methods and perioperative care have decreased morbidity and mortality rates. In this study, postoperative QoL after resection of benign or malignant liver tumours was evaluated. Methods: In this single‐centre study, QoL was evaluated prospectively using the European Organisation for Research and Treatment of Cancer QLQ‐C30 and the liver‐specific QLQ‐LMC21 module before, and 1, 3, 6 and 12 months after open or laparoscopic liver surgery. Results: Between June 2007 and January 2013, 188 patients (130 with malignant and 58 with benign tumours) requiring major liver resection were included. Global health status was no different between the two groups before and 1 month after liver resection. All patients showed an improvement in global health status at 3, 6 and 12 months after surgery. Patients with benign tumours had better global health status than those with malignant tumours at these time points ( P < 0·001, P = 0·002 and P = 0·006 respectively). Patients with benign disease had better physical function scores ( P = 0·011, P = 0·025 and P = 0·041) and lower fatigue scores ( P = 0·001, P = 0·002 and P = 0·002) at 3, 6 and 12 months than those with malignant disease. Conclusion: This study confirmed overall good QoL in patients undergoing liver resection for benign or malignant tumours, which improved after surgery. Benign diseases were associated with better short‐ and long‐term QoL scores. Abstract : Acceptable